2011
DOI: 10.1055/s-0030-1265203
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Cost of Running Barefoot vs. Running Shod

Abstract: The purpose of this study was to investigate the oxygen cost of running barefoot vs. running shod on the treadmill as well as overground. 10 healthy recreational runners, 5 male and 5 female, whose mean age was 23.8±3.39 volunteered to participate in the study. Subjects participated in 4 experimental conditions: 1) barefoot on treadmill, 2) shod on treadmill, 3) barefoot overground, and 4) shod overground. For each condition, subjects ran for 6 min at 70% vVO (2)max pace while VO (2), heart rate (HR), and rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 42 publications
4
91
2
1
Order By: Relevance
“…Besides the surface, the use of different types of footwear may have influenced on the findings of the present study. Di Michele et al 14 , when compared the anaerobic threshold of 18 soccer players determined on treadmill and on natural grass did not observe significant differences when sneakers were worn at the two situations. However, Kunduracioglu et al 13 determined that field soccer players may present lower anaerobic threshold values, determined on field with cleats compared with the one determined on treadmill and wearing sneakers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides the surface, the use of different types of footwear may have influenced on the findings of the present study. Di Michele et al 14 , when compared the anaerobic threshold of 18 soccer players determined on treadmill and on natural grass did not observe significant differences when sneakers were worn at the two situations. However, Kunduracioglu et al 13 determined that field soccer players may present lower anaerobic threshold values, determined on field with cleats compared with the one determined on treadmill and wearing sneakers.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, many studies have demonstrated the influence of different surfaces on the energy expenditure [10][11][12] and on the determination of physiological variables 13,14 as well as of exercise performed barefoot or with footwear 15 . Moreover, Brechue et al 16 observed significant differences in the 40 m maximal performance on grass and on firmer surfaces, demonstrating hence the influence of different surfaces also on efforts with anaerobic predominance.…”
Section: Introductionmentioning
confidence: 99%
“…The velocity of the treadmill belt was validated prior to data collection in accordance with Sinclair et al (2014). In agreement with the procedure documented by Hanson et al (2010), participants were required to undertake a 3 min habituation period in all footwear conditions, during which they ran at the required velocity prior to the commencement of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Their observations showed that running in minimalist footwear was associated with significant improvements in running economy compared to conventional footwear. Similarly, Hanson et al (2010) showed that barefoot running was more economical in comparison to shod. However, as shoe mass is known to increase the oxygen cost of running for a given velocity (Frederick et al, 1986); studies of this nature have been scrutinised as minimalist footwear are typically much lighter.…”
Section: Demonstrated That Runningmentioning
confidence: 98%
See 1 more Smart Citation